Жизненный цикл Prosthorhynhus cylindraceus (Acanthocephala, Plagiorhynchidae) в Палеарктике - Лисицына, О.И. (Вестник зоологии, 1993)
Life cycle of Prosthorhynchus cylindraceus has been first studied in Palearctic. The development of larvae in intermediate host completes for 60—65 days. Pairing of puberal individuals occurs in 11—12 days, the onset of egg laying by female — in 21—25 days. Descriptions and figures of all the stages are presented.